Clinical significance of serum cortisol levels following surgery for congenital heart disease. (29th April 2016) - Teagarden, Alicia M.; Mastropietro, Christopher W.
Abstract: Objective: Use of hydrocortisone to treat refractory haemodynamic instability in patients recovering from surgery for congenital heart disease is common practice at many centres. We aimed to determine whether there is a relationship between total serum cortisol concentrations and haemodynamic response to this therapy. Material and methods: We retrospectively reviewed patients <21 years who underwent cardiac surgery from 2011 to 2013, received hydrocortisone within 72 hours postoperatively, and had total serum cortisol measurements contemporaneous with its administration. Favourable responders were defined as patients in whom, at 24 hours after hydrocortisone initiation, either (1) systolic blood pressure was increased or unchanged and vasoactive-inotrope score was decreased or (2) systolic blood pressure increased by ⩾10% of baseline and vasoactive-inotrope score was unchanged. Variables were compared using t-tests or Mann–Whitney U tests as appropriate. Results: In total, 24 patients were reviewed, with a median age of 1.4 months and range of 0.1–232 months. Among them, 14 (58%) patients responded favourably to hydrocortisone. At 24 hours, the median change in vasoactive-inotrope score was −18% in favourable responders and +31% in those who did not respond favourably, p = 0.001. The mean pre-hydrocortisone total serum cortisol in favourable responders was 17.4±10.9 µg/dl compared with 46.1±44.7 µg/dl in those who did not respond favourably, p = 0.03. Conclusion: Total serum cortisol obtained before initiation of hydrocortisone was significantly lower in patients who responded favourably to this therapy. Total serum cortisol may therefore be helpful in identifying children recovering from cardiac surgery who may or may not haemodynamically improve with hydrocortisone.